2008
DOI: 10.1063/1.2883943
|View full text |Cite
|
Sign up to set email alerts
|

Relation between growth dynamics and the spatial distribution of intrinsic defects in self-assembled colloidal crystal films

Abstract: Articles you may be interested inOptical studies of random disorder of colloidal photonic crystals and its evolution in evaporation induced selfassembly J. Chem. Phys. 137, 234111 (2012) Modifying the growth of organic thin films by a self-assembled monolayer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In this sense, we have recently shown that some important structural features of colloidal crystal films can be understood using a model that describes, in terms of the experimental variables, the deposition of the colloidal particle film onto a vertical or tilted flat substrate. 19 , 20 We confirmed that, for an evaporating colloidal suspension in which the evaporation velocity exceeds the sedimentation velocity, particles accumulate at the solvent-air interface and this gives rise to an increase of the thickness when analysed over long distances, as it has been previously proposed. 21 At the same time, we found that during evaporation the motion of the contact line resembles stick-slip motion and shifts downwards following an undulating dependence with time.…”
Section: Growth Dynamics Of Colloidal Crystal Filmssupporting
confidence: 85%
See 1 more Smart Citation
“…In this sense, we have recently shown that some important structural features of colloidal crystal films can be understood using a model that describes, in terms of the experimental variables, the deposition of the colloidal particle film onto a vertical or tilted flat substrate. 19 , 20 We confirmed that, for an evaporating colloidal suspension in which the evaporation velocity exceeds the sedimentation velocity, particles accumulate at the solvent-air interface and this gives rise to an increase of the thickness when analysed over long distances, as it has been previously proposed. 21 At the same time, we found that during evaporation the motion of the contact line resembles stick-slip motion and shifts downwards following an undulating dependence with time.…”
Section: Growth Dynamics Of Colloidal Crystal Filmssupporting
confidence: 85%
“…Other groups have recently reported thorough analyses of the variations of crystal thickness along the growth direction 21,24 or of the relation between crystal thickness and defect density or domain size, 25,26 such observations being in fair agreement with those reported in Refs. [19,20].…”
Section: Growth Dynamics Of Colloidal Crystal Filmsmentioning
confidence: 98%
“…[21][22][23][24][25][26][27][28][29][30] These valuable results are also promising to produce high quality crystals inside capillaries. Among these parameters, evaporation temperature is most important due to its decision of evaporation rate of solvent and film growth rate, which can keep the balance of the rate of nucleus formation, particle transport, and crystallization.…”
Section: Resultsmentioning
confidence: 91%
“…18,19 To develop our model, we adapted deposition models previously developed to understand the structural properties of films formed from the drying of colloidal suspension drops on flat substrates. 20 From our model, whose full details can be found in ref.…”
Section: Growth Dynamics Of Colloidal Crystal Filmsmentioning
confidence: 99%